The Construction of Pre-service English Teachers’ Identity: Attitudes toward Indonesian English - Sri Imelwaty; Riang Abrit; Edwar Kemal (Langkawi: Journal of The Association for Arabic and English, 2022)
Drawing from World Englishes (WE) perspective, English language learners need to agree with the varieties of English. This study investigates the attitudes of pre-service English teachers or students majoring in English Education study programs in Indonesia and its relation to their identity construction in English Language Teaching (ELT). Survey research was conducted, and the data were quantitatively collected with an online questionnaire completed by 198 respondents. The findings showed the positive attitudes of pre-service English teachers toward Indonesian English and their interest in incorporating Indonesian norms and culture into ELT. However, most pre-service English teachers wanted to sound like Native Speakers of English (NSE) even though having positive attitudes toward Indonesian English, and they wanted to be taught by teachers from both Indonesia and native speakers. The findings suggest the importance of raising the agreement of WE by reforming ELT pedagogically in contexts where local varieties of English are emerging